Effects of fiber loading and chemical treatments on properties of sisal fiber-reinforced sheet molding compounds. (September 2017) - Huang, Zhen; Ge, Heyi; Yin, Jiaojiao; Liu, Fanggang
In this study, the effects of fiber loading from 0 vol.% to 15 vol.% and the chemical treatments on the properties of the sisal fiber-reinforced sheet molding compounds were investigated. The chemical treatments were performed with alkali, γ-ammoniapropyl-triethoxy-silane (KH-550) and γ-methacryloxypropyl-trimethoxy-sliane (KH-570), respectively, to improve the interfacial adhesion between sisal fiber and the matrix (unsaturated polyester resin). The changes of surface morphology and sisal fiber functional groups were investigated by scanning electron microscopy and Fourier transform infrared spectroscopic analysis, respectively. Compared to the untreated sisal fiber-reinforced sheet molding compounds, the mechanical property of the treated sisal fiber-reinforced sheet molding compounds increased due to the interfacial enhancement between sisal fiber and the matrix, which could be observed through the scanning electron microscopy images of fracture surface. Moreover, the better interfacial adhesion was also assisted in water absorption resistance and the thermal stability of the treated sisal fiber-reinforced sheet molding compounds. In the chemical treatments, KH-570 treatment was proved to be an effective method to improve the interfacial adhesion between sisal fiber and the matrix.